Development of sorbic acid microcapsules and application in starch‐poly (butylene adipate co‐terephthalate) films. Issue 5 (5th April 2021) - Oliveira, Catarina de M.; Gomes, Brenda de O.; Batista, Andreia F. P.; Mikcha, Jane M. G.; Yamashita, Fabio; Scapim, Mônica R. S.; Bergamasco, Rita de C.
Abstract: Sorbic acid (SA) microcapsules were prepared by molecular inclusion in β‐cyclodextrin, aiming to improve the physical properties of the acid, in order to facilitate its applicability in the formulation of PBAT films, obtained by extrusion. FTIR, DSC, and NMR‐H 1 methods verified the interaction between SA and β‐cyclodextrin molecules and the formation of the inclusion complex. A thermal stability test showed that the microencapsulated SA can withstand film production temperatures. Starch films were elaborated by extrusion, using SA in free form (F1) and microencapsulated form (F2), and submitted to water vapor permeability, with no significant difference between formulations. As to mechanical properties, the F2 formulation presented significantly lower tensile strength and modulus of elasticity when compared to F1. The films were submitted to SA release test and showed the highest amount of SA when microencapsulated, with controlled release of the compound, evidencing the efficiency of SA microencapsulation for application in extruded films. Novelty impact statement: Sorbic acid (SA) microcapsules were produced by the molecular inclusion method in β‐CD and incorporated into starch‐poly (butylene adipate co‐terephthalate) (PBAT) films obtained by extrusion. The films produced with inclusion complex presented alterations in mechanical properties and color, due to the addition of β‐CD in the formulation. The microencapsulation protected SA during film preparation, reducing its sublimation at high temperatures, and provided a controlled release of SA.